Master Plan Wisata Desa Segoroyoso, Kapanewon Pleret, Kabupaten Bantul - Setiadi, Amos; Sekarlangit, Nimas; Sthepan, Theodorus; Anggarajati (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Kapanewon Pleret is one of the areas with an element of tourism, considering its location and state, primarily hills; besides that, there are many other potentials, including hilly nature tourism and the Suharto monument. The arrangement of the Segoroyoso Tourism Area is carried out with the stages and methods of preparation, including the preparation of an activity plan; Collecting data, both primary data and secondary data, through field observations, measuring the site, documentation, and interviews; Study of literature on the concept of site design, natural tourism areas, spatial regulations in Bantul Regency; Qualitative descriptive data analysis; and the concept and design of the Master Plan. The design of supporting facilities involves the role of residents as active managers of the Pangul hill area and the Suharto monument. The community's commitment is very good with the efforts that have been made in the form of providing supporting facilities independently. Citizens' awareness and response to this tourism potential will benefit from increasing welfare through community involvement in managing this tourism potential. The Segoroyoso tourist area is expected to develop as an attractive and sustainable natural tourism destination.